The Impact of Social Inequality on Educational Quality in Indonesia: Challenges and Policy Recommendations - Mujiburrohman; Deliana Putri (Walidem Institute and Publishing (WIP), 2025)
Objective: This study aims to analyze the impact of social inequality on the quality of education in Indonesia. The research focuses on identifying examples of inequality, analyzing the contributing factors, and evaluating strategic efforts to address this issue. Theoretical framework: The theoretical framework employed is the theory of social inequality, which highlights the relationship between economic disparities, access to education, and human resource development. Literature Review: The literature review encompasses various studies discussing educational budget allocation, government programs, and the correlation between socioeconomic status and access to quality education in Indonesia. Methods: The research adopts a qualitative approach with descriptive analysis techniques. Data were collected through document analysis, interviews with educational stakeholders, and analysis of official government reports related to educational budget allocation. Results: The findings reveal that despite the government allocating 20% of the national budget (APBN) for education, significant gaps persist in access to and the quality of education, particularly in remote areas and among low-income communities. Key contributing factors include economic disparities, unequal distribution of resources, and weak educational infrastructure. Implications: The implications of these findings highlight the need for more targeted policy strategies, such as equitable redistribution of educational funds, improved access to educational technology, and enhanced teacher capacity in underdeveloped regions. This study offers a novel contribution by integrating a data-driven and social inequality theoretical approach to identify innovative and sustainable solutions. Novelty: The novelty of this research lies in its multidimensional analysis, combining social, economic, and educational aspects to provide more comprehensive policy recommendations. The findings are expected to serve as a reference for policymakers in improving the quality of national education to create intelligent and competitive human resources for the future.